The Mizar article:

Parallelity Spaces

by
Eugeniusz Kusak,
Wojciech Leonczuk, and
Michal Muzalewski

Received November 23, 1989

Copyright (c) 1989 Association of Mizar Users

MML identifier: PARSP_1
[ MML identifier index ]


environ

 vocabulary VECTSP_1, RLVECT_1, ARYTM_1, RELAT_1, BINOP_1, FUNCT_1, MCART_1,
      PARSP_1;
 notation TARSKI, XBOOLE_0, ZFMISC_1, SUBSET_1, MCART_1, DOMAIN_1, FUNCT_2,
      BINOP_1, STRUCT_0, RLVECT_1, VECTSP_1;
 constructors DOMAIN_1, BINOP_1, VECTSP_1, MEMBERED, XBOOLE_0;
 clusters STRUCT_0, SUBSET_1, VECTSP_1, MEMBERED, ZFMISC_1, XBOOLE_0;
 requirements SUBSET, BOOLE;
 definitions TARSKI, STRUCT_0;
 theorems MCART_1, VECTSP_1, BINOP_1, FUNCT_2, TARSKI, RLVECT_1;
 schemes BINOP_1, FUNCT_2, XBOOLE_0;

begin

reserve F for Field, a,b,c,d,e,f,g,h for Element of F;

Lm1:
 for F being add-associative right_zeroed
                 right_complementable (non empty LoopStr),
     a, b being Element of F holds
  -(a-b) = b-a
  proof
 let F be add-associative right_zeroed
                 right_complementable (non empty LoopStr),
     a, b be Element of F;
  thus -(a-b) = b+-a by RLVECT_1:47 .= b-a by RLVECT_1:def 11;
  end;

Lm2:  (a-b)*(c-d) - (b-a)*(d-c) = 0.F
 proof -(a-b) = b-a & -(c-d) = d-c by Lm1;
  then (a-b)*(c-d)-(b-a)*(d-c)=(a-b)*(c-d)-((a-b)*(c-d)) by VECTSP_1:42;
  hence thesis by RLVECT_1:28;
 end;

Lm3: a*(b-b) - (c-c)*d = 0.F
 proof b-b = 0.F & c-c = 0.F by RLVECT_1:28;
  then a*(b-b) = 0.F & (c-c)*d = 0.F by VECTSP_1:39;
  hence thesis by RLVECT_1:28;
 end;

Lm4: a <> 0.F & a*e - d*b = 0.F & a*c - h*b = 0.F implies d*c - h*e = 0.F
 proof assume a <> 0.F & a*e - d*b = 0.F & a*c - h*b = 0.F;
  then e = d*b*a" & c = h*b*a" by VECTSP_1:88;
  then e = d*(b*a") & c = h*(b*a") by VECTSP_1:def 16;
  then h*e = (h*d)*(b*a") & d*c = (d*h)*(b*a") & d*h =h*d
   by VECTSP_1:def 16;
  hence d*c - h*e = 0.F by RLVECT_1:28;
 end;

Lm5: a*b - c*d = 0.F implies d*c - b*a = 0.F
   proof
     assume a*b - c*d = 0.F;
then A1:   -(a*b - c*d) = 0.F by RLVECT_1:25;
     thus d*c - b*a = d*c + -(b*a) by RLVECT_1:def 11
       .= 0.F by A1,RLVECT_1:47;
   end;

Lm6: b <> 0.F & a*e - d*b = 0.F & a*c - h*b = 0.F implies d*c - h*e = 0.F
 proof assume b <> 0.F;
  then b*d - e*a = 0.F & b*h - c*a = 0.F implies e*h - c*d = 0.F by Lm4;
  hence thesis by Lm5;
 end;

Lm7: (c*d)*(a*b) = ((a*c)*d)*b
 proof
  thus (c*d)*(a*b) = (a*(c*d))*b by VECTSP_1:def 16
    .= ((a*c)*d)*b by VECTSP_1:def 16;
 end;

Lm8: a*b - c*d = 0.F implies (a*f*g*b) - (c*f*g*d) = 0.F
 proof assume A1: a*b - c*d = 0.F;
    (a*f*g*b) = (f*g)*(a*b) & (c*f*g*d) = (f*g)*(c*d) by Lm7;
  hence (a*f*g*b) - (c*f*g*d) = (f*g)*(a*b - c*d) by VECTSP_1:43
     .= 0.F by A1,VECTSP_1:39;
 end;

Lm9: (a-b)*(c-d) = a*c + (-a*d +-(b*(c-d)))
  proof
   thus (a-b)*(c-d) = (a+-b)*(c-d) by RLVECT_1:def 11
                   .= a*(c-d)+(-b)*(c-d) by VECTSP_1:def 18
                   .= a*(c-d)+-b*(c-d) by VECTSP_1:41
                   .= (a*c-a*d)+-b*(c-d) by VECTSP_1:43
                   .= (a*c+-a*d)+-b*(c-d) by RLVECT_1:def 11
                   .= a*c + (-a*d +-(b*(c-d))) by RLVECT_1:def 6;
  end;

Lm10: (a+b)+(c+d) = a+(b+c)+d
 proof
   thus (a+b)+(c+d) = (a+b)+c+d by RLVECT_1:def 6 .= a+(b+c)+d by RLVECT_1:def
6;
 end;

 Lm11:
 for F being add-associative right_zeroed
                     right_complementable (non empty LoopStr),
     a, b, c being Element of F holds
  (b+a)-(c+a) = b-c
 proof let F be add-associative right_zeroed
                     right_complementable (non empty LoopStr),
    a,b,c be Element of F;
    thus (b+a)-(c+a) = (b+a)+-(c+a) by RLVECT_1:def 11
                    .= (b+a)+(-a+-c) by RLVECT_1:45
                    .= ((b+a)+-a)+-c by RLVECT_1:def 6
                    .= (b+(a+-a))+-c by RLVECT_1:def 6
                    .= (b+0.F)+-c by RLVECT_1:def 10
                    .= b+-c by RLVECT_1:10
                    .= b-c by RLVECT_1:def 11;
 end;

Lm12:
 for F being add-associative right_zeroed
                          right_complementable (non empty LoopStr),
     a, b being Element of F holds
  a + b = -(-b + -a)
 proof let F be add-associative right_zeroed
                         right_complementable (non empty LoopStr),
   a,b be Element of F;
  thus a + b = --(a + b) by RLVECT_1:30 .= -(-b + -a) by RLVECT_1:45;
 end;

Lm13: (a-b)*(c-d)-(a-e)*(c-f) = 0.F implies (b-a)*(f-d)-(b-e)*(f-c) = 0.F
 proof assume A1: (a-b)*(c-d)-(a-e)*(c-f) = 0.F;
A2: (a-b)*(c-d) = a*c+(-a*d+-(b*(c-d))) & (a-e)*(c-f) = a*c+(-a*f+-(e*(c-f)))
     by Lm9;
    (b-a)*(f-d) = b*f+(-b*d+-(a*(f-d))) & (b-e)*(f-c) = b*f +(-b*c+-(e*(f-c)))
    by Lm9;
  hence (b-a)*(f-d)-(b-e)*(f-c)
       = (-b*d+-(a*(f-d)))-(-b*c+-(e*(f-c))) by Lm11
      .= (-b*d+-(a*f-a*d))-(-b*c+-(e*(f-c))) by VECTSP_1:43
      .= (-b*d+(-a*f+a*d))-(-b*c+-(e*(f-c))) by RLVECT_1:47
      .= ((-b*d+a*d)+-a*f)-(-b*c+-(e*(f-c))) by RLVECT_1:def 6
      .= ((a*d+-b*d)+-a*f)+-(-b*c+-(e*(f-c))) by RLVECT_1:def 11
      .= ((a*d+-b*d)+-a*f)+(--b*c+--(e*(f-c))) by RLVECT_1:45
      .= ((a*d+-b*d)+-a*f)+(b*c+--(e*(f-c))) by RLVECT_1:30
      .= ((a*d+-b*d)+-a*f)+(b*c+(e*(f-c))) by RLVECT_1:30
      .= ((a*d+-b*d)+(-a*f+b*c))+(e*(f-c)) by Lm10
      .= ((a*d+-b*d)+b*c)+(-a*f+(e*(f-c))) by Lm10
      .= (a*d+(-b*d+b*c))+(-a*f+(e*(f-c))) by RLVECT_1:def 6
      .= (a*d+(b*c-b*d))+(-a*f+(e*(f-c))) by RLVECT_1:def 11
      .= (a*d+b*(c-d))+(-a*f+(e*(f-c))) by VECTSP_1:43
      .= -(-a*d+-b*(c-d))+(-a*f+(e*(f-c))) by Lm12
      .= -(-a*d+-b*(c-d))+-(--a*f+-(e*(f-c))) by Lm12
      .= -(-a*d+-b*(c-d))+-(a*f+-(e*(f-c))) by RLVECT_1:30
      .= -((-a*d+-b*(c-d))+(a*f+-(e*(f-c)))) by RLVECT_1:45
      .= -((-a*d+-b*(c-d))+-(-a*f+--(e*(f-c)))) by Lm12
      .= -((-a*d+-b*(c-d))-(-a*f+--(e*(f-c)))) by RLVECT_1:def 11
      .= -((-a*d+-b*(c-d))-(-a*f+-((-(f-c))*e))) by VECTSP_1:41
      .= -((-a*d+-b*(c-d))-(-a*f+-(e*(c-f)))) by Lm1
      .= - 0.F by A1,A2,Lm11
      .= 0.F by RLVECT_1:25;
end;

Lm14:  a-(a+b+-c) = c-b
 proof
  thus a-(a+b+-c) = a-(a+(b+-c)) by RLVECT_1:def 6
                 .= a-(a+(b-c)) by RLVECT_1:def 11
                 .= a+-(a+(b-c)) by RLVECT_1:def 11
                 .= a+(-a+-(b-c)) by RLVECT_1:45
                 .= (a+-a)+-(b-c) by RLVECT_1:def 6
                 .= 0.F + -(b-c) by RLVECT_1:def 10
                 .= -(b-c) by RLVECT_1:10
                 .= c-b by Lm1;

 end;

Lm15: (a-b)*(c-(c+h+-g))-(e-(e+b+-a))*(g-h) = 0.F
 proof c-(c+h+-g) = g-h & e-(e+b+-a) = a-b by Lm14;
  hence thesis by RLVECT_1:28;
 end;

::
::               1. A THREE-DIMENSION CARTESIAN GROUP
::

reserve x,y
   for Element of [:the carrier of F,the carrier of F,the carrier of F:];

deffunc 3F(Field) = [:the carrier of $1,the carrier of $1,the carrier of $1:];

 definition let F;
  func c3add(F) ->
   BinOp of [:the carrier of F,the carrier of F,the carrier of F:] means
   :Def1: it.(x,y) = [x`1+y`1,x`2+y`2,x`3+y`3];
  existence
  proof
   deffunc O(Element of 3F(F),Element of 3F(F)) =
    [$1`1+$2`1,$1`2+$2`2,$1`3+$2`3];
   consider f be BinOp of 3F(F) such that
    A1: f.(x,y) = O(x,y) from BinOpLambda;
   take f;
   thus thesis by A1;
  end;
  uniqueness
   proof let f,g be BinOp of 3F(F) such that
    A2: f.(x,y) = [x`1+y`1,x`2+y`2,x`3+y`3] and
    A3: g.(x,y) = [x`1+y`1,x`2+y`2,x`3+y`3];
      f.(x,y) = g.(x,y)
     proof thus f.(x,y)=[x`1+y`1,x`2+y`2,x`3+y`3] by A2 .= g.(x,y) by A3; end;
    hence f = g by BINOP_1:2;
   end;
  end;

definition let F,x,y;
 func x+y -> Element of
     [:the carrier of F,the carrier of F,the carrier of F:] equals
 :Def2:  (c3add(F)).(x,y);
 coherence;
end;

canceled 2;

theorem
Th3: x+y = [x`1+y`1,x`2+y`2,x`3+y`3]
 proof
  thus x+y = (c3add(F)).(x,y) by Def2
          .= [x`1+y`1,x`2+y`2,x`3+y`3] by Def1;
 end;

theorem
Th4: [a,b,c]+[f,g,h]=[a+f,b+g,c+h]
 proof set abc = [a,b,c] ,fgh = [f,g,h];
    abc`1=a & abc`2=b & abc`3=c & fgh`1=f & fgh`2=g & fgh`3=h by MCART_1:47;
  hence thesis by Th3;
 end;

definition let F;
 func c3compl(F) ->
  UnOp of [:the carrier of F,the carrier of F,the carrier of F:] means
  :Def3: it.(x) = [-x`1,-x`2,-x`3];
 existence
 proof
  deffunc O(Element of 3F(F)) = [-$1`1,-$1`2,-$1`3];
  consider f be UnOp of 3F(F) such that
   A1: f.(x) = O(x) from LambdaD;
  take f;
  thus thesis by A1;
 end;
 uniqueness
  proof let f,g be UnOp of 3F(F) such that
   A2:  f.(x) = [-x`1,-x`2,-x`3] and A3: g.(x) = [-x`1,-x`2,-x`3];
     f.(x) = g.(x)
    proof thus f.(x) = [-x`1,-x`2,-x`3] by A2 .= g.(x) by A3; end;
   hence f = g by FUNCT_2:113;
  end;
 end;

definition let F,x;
 func -x -> Element of
   [:the carrier of F,the carrier of F,the carrier of F:] equals
 :Def4:  (c3compl(F)).(x);
 coherence;
end;

canceled 2;

theorem
Th7: -x = [-x`1,-x`2,-x`3]
 proof
  thus -x = (c3compl(F)).(x) by Def4 .= [-x`1,-x`2,-x`3] by Def3;
 end;

::
::                      2. PARALLELITY STRUCTURE
::


reserve S for set;

definition let S;
 mode Relation4 of S -> set means
 :Def5: it c= [:S,S,S,S:];
 existence;
end;

definition
  struct(1-sorted) ParStr (# carrier -> set,
                      4_arg_relation -> Relation4 of the carrier #);
end;

definition
 cluster non empty ParStr;
 existence
  proof
    consider A being non empty set, R being Relation4 of A;
   take ParStr(#A,R#);
   thus the carrier of ParStr(#A,R#) is non empty;
  end;
end;

reserve F for Field;
reserve PS for non empty ParStr;

definition let PS;
 let a,b,c,d be Element of PS;
 pred a,b '||' c,d means
 :Def6: [a,b,c,d] in the 4_arg_relation of PS;
end;

definition let F;
 func C3(F) -> set equals
 :Def7:  [:the carrier of F,the carrier of F,the carrier of F:];
 coherence;
end;

definition let F;
 cluster C3(F) -> non empty;
 coherence
 proof
     C3(F) = [:the carrier of F,the carrier of F,the carrier of F:] by Def7;
   hence thesis;
 end;
end;

definition let F;
 func 4C3(F) -> set equals
 :Def8:  [:C3(F),C3(F),C3(F),C3(F):];
 coherence;
end;

definition let F;
 cluster 4C3(F) -> non empty;
 coherence
 proof
     4C3 F = [:C3(F),C3(F),C3(F),C3(F):] by Def8;
   hence thesis;
 end;
end;

reserve x for set, a,b,c,d,e,f,g,h,i,j,k,l for
   Element of [:the carrier of F,the carrier of F,the carrier of F:];

definition let F;
 func PRs(F) -> set means
 :Def9: x in it iff x in 4C3(F) &
  ex a,b,c,d st x = [a,b,c,d] &
  (a`1-b`1)*(c`2-d`2) - (c`1-d`1)*(a`2-b`2) = 0.F &
  (a`1-b`1)*(c`3-d`3) - (c`1-d`1)*(a`3-b`3) = 0.F &
  (a`2-b`2)*(c`3-d`3) - (c`2-d`2)*(a`3-b`3) = 0.F;
 existence
 proof
  defpred P[set] means
   ex a,b,c,d st $1 = [a,b,c,d] &
   (a`1-b`1)*(c`2-d`2) - (c`1-d`1)*(a`2-b`2) = 0.F &
   (a`1-b`1)*(c`3-d`3) - (c`1-d`1)*(a`3-b`3) = 0.F &
   (a`2-b`2)*(c`3-d`3) - (c`2-d`2)*(a`3-b`3) = 0.F;
  thus ex X be set st for x be set holds x in X iff x in 4C3(F) & P[x]
   from Separation;
 end;
 uniqueness
  proof
   defpred CB[set] means $1 in 4C3(F) &
     ex a,b,c,d st $1 = [a,b,c,d] &
      (a`1-b`1)*(c`2-d`2) - (c`1-d`1)*(a`2-b`2) = 0.F &
      (a`1-b`1)*(c`3-d`3) - (c`1-d`1)*(a`3-b`3) = 0.F &
      (a`2-b`2)*(c`3-d`3) - (c`2-d`2)*(a`3-b`3) = 0.F;
   let H1,H2 be set such that A1: x in H1 iff CB[x] and A2: x in H2 iff CB[x];
     x in H1 iff x in H2 proof x in H1 iff CB[x] by A1; hence thesis by A2;
end;
   hence H1 = H2 by TARSKI:2;
  end;
end;

canceled 5;

theorem
Th13: PRs(F) c= [:C3(F),C3(F),C3(F),C3(F):]
 proof let x; 4C3(F) = [:C3(F),C3(F),C3(F),C3(F):] by Def8;
  hence thesis by Def9;
 end;

definition let F;
 func PR(F) -> Relation4 of C3(F) equals
 :Def10:  PRs(F);
 coherence
  proof PRs(F) c= [:C3(F),C3(F),C3(F),C3(F):] by Th13;
   hence thesis by Def5;
  end;
end;

definition let F;
 func MPS(F) -> ParStr equals
 :Def11:  ParStr (# C3(F),PR(F) #);
 correctness;
end;

definition let F;
 cluster MPS(F) -> strict non empty;
 coherence
  proof
      MPS(F) = ParStr (# C3(F),PR(F) #) by Def11;
   hence MPS F is strict & the carrier of MPS F is non empty;
  end;
end;

canceled 2;

theorem
Th16: the carrier of MPS(F) = C3(F)
 proof MPS(F) = ParStr (# C3(F),PR(F) #) by Def11; hence thesis; end;

theorem
Th17: the 4_arg_relation of MPS(F) = PR(F)
 proof MPS(F) = ParStr (# C3(F),PR(F) #) by Def11; hence thesis; end;

reserve a,b,c,d,p,q,r,s for Element of MPS(F);

theorem
Th18: a,b '||' c,d iff [a,b,c,d] in PR(F)
 proof the 4_arg_relation of MPS(F) = PR(F) by Th17;
  hence thesis by Def6;
 end;

theorem
Th19: [a,b,c,d] in PR(F) iff ([a,b,c,d] in 4C3(F) &
     ex e,f,g,h st [a,b,c,d] = [e,f,g,h] &
      (e`1-f`1)*(g`2-h`2) - (g`1-h`1)*(e`2-f`2) = 0.F &
      (e`1-f`1)*(g`3-h`3) - (g`1-h`1)*(e`3-f`3) = 0.F &
      (e`2-f`2)*(g`3-h`3) - (g`2-h`2)*(e`3-f`3) = 0.F)
 proof PR(F) = PRs(F) by Def10; hence thesis by Def9; end;

theorem
Th20: a,b '||' c,d iff ([a,b,c,d] in 4C3(F) &
     ex e,f,g,h st [a,b,c,d] = [e,f,g,h] &
      (e`1-f`1)*(g`2-h`2) - (g`1-h`1)*(e`2-f`2) = 0.F &
      (e`1-f`1)*(g`3-h`3) - (g`1-h`1)*(e`3-f`3) = 0.F &
      (e`2-f`2)*(g`3-h`3) - (g`2-h`2)*(e`3-f`3) = 0.F)
 proof a,b '||' c,d iff [a,b,c,d] in PR(F) by Th18; hence thesis by Th19; end
;

theorem
Th21: the carrier of MPS(F) =
             [:the carrier of F,the carrier of F,the carrier of F:]
 proof 3F(F) = C3(F) by Def7; hence thesis by Th16; end;

theorem
Th22: [a,b,c,d] in 4C3(F)
 proof the carrier of MPS(F) = C3(F) & 4C3(F) = [:C3(F),C3(F),C3(F),C3(F):]
     by Def8,Th16;
  hence thesis;
 end;

theorem
Th23: a,b '||' c,d iff ex e,f,g,h st [a,b,c,d] = [e,f,g,h] &
        (e`1-f`1)*(g`2-h`2) - (g`1-h`1)*(e`2-f`2) = 0.F &
        (e`1-f`1)*(g`3-h`3) - (g`1-h`1)*(e`3-f`3) = 0.F &
        (e`2-f`2)*(g`3-h`3) - (g`2-h`2)*(e`3-f`3) = 0.F
 proof [a,b,c,d] in 4C3(F) by Th22; hence thesis by Th20; end;

theorem
Th24: a,b '||' b,a
 proof the carrier of MPS(F) = 3F(F) by Th21;
  then consider e,f such that A1: [e,f,f,e] = [a,b,b,a];
    (e`1-f`1)*(f`2-e`2) - (f`1-e`1)*(e`2-f`2) = 0.F &
  (e`1-f`1)*(f`3-e`3) - (f`1-e`1)*(e`3-f`3) = 0.F &
  (e`2-f`2)*(f`3-e`3) - (f`2-e`2)*(e`3-f`3) = 0.F by Lm2;
  hence thesis by A1,Th23;
 end;

theorem
Th25: a,b '||' c,c
 proof the carrier of MPS(F) = 3F(F) by Th21;
  then consider e,f,g such that A1: [e,f,g,g] = [a,b,c,c];
    (e`1-f`1)*(g`2-g`2) - (g`1-g`1)*(e`2-f`2) = 0.F &
  (e`1-f`1)*(g`3-g`3) - (g`1-g`1)*(e`3-f`3) = 0.F &
  (e`2-f`2)*(g`3-g`3) - (g`2-g`2)*(e`3-f`3) = 0.F by Lm3;
  hence thesis by A1,Th23;
 end;

theorem
Th26: a,b '||' p,q & a,b '||' r,s implies p,q '||' r,s or a=b
 proof
  defpred CB[(Element of 3F(F)),(Element of 3F(F)),
          (Element of 3F(F)),Element of 3F(F)]
    means ($1`1-$2`1)*($3`2-$4`2) - ($3`1-$4`1)*($1`2-$2`2) = 0.F &
          ($1`1-$2`1)*($3`3-$4`3) - ($3`1-$4`1)*($1`3-$2`3) = 0.F &
          ($1`2-$2`2)*($3`3-$4`3) - ($3`2-$4`2)*($1`3-$2`3) = 0.F;
  assume A1: a,b '||' p,q & a,b '||' r,s;

  then consider e,f,g,h such that
  A2:  [e,f,g,h] = [a,b,p,q] and A3: CB[e,f,g,h] by Th23;
  consider i,j,k,l such that
  A4:  [i,j,k,l] = [a,b,r,s] and A5: CB[i,j,k,l] by A1,Th23;
  A6: e = a & f = b & g = p & h = q & i = a & j = b & k = r & l = s
    by A2,A4,MCART_1:33;
  set A = e`1-f`1, B = e`2-f`2, C = e`3-f`3,
      D = g`1-h`1, E = g`2-h`2, K = g`3-h`3,
      G = k`1-l`1, H = k`2-l`2, I = k`3-l`3;
     now assume A7: a <> b;
      now e = [e`1,e`2,e`3] & f = [f`1,f`2,f`3] by MCART_1:48;
     then A8: e`1 <> f`1 or e`2 <> f`2 or e`3 <> f`3 by A6,A7;
     per cases by A8,RLVECT_1:35;
     case A9: A <> 0.F;
      hence D*H-G*E = 0.F by A3,A5,A6,Lm4;
      thus A10: D*I-G*K = 0.F by A3,A5,A6,A9,Lm4;
        E*I = ((D*B)*A")*I & H*K = ((G*B)*A")*K by A3,A5,A6,A9,VECTSP_1:88;
      hence E*I-H*K = 0.F by A10,Lm8;
     case A11: B <> 0.F;
      hence D*H-G*E = 0.F by A3,A5,A6,Lm6;
      thus A12: E*I-H*K = 0.F by A3,A5,A6,A11,Lm4;
        D*I = ((E*A)*B")*I & G*K = ((H*A)*B")*K by A3,A5,A6,A11,VECTSP_1:88;
      hence D*I-G*K = 0.F by A12,Lm8;
     case A13: C <> 0.F;
      hence E*I-H*K = 0.F by A3,A5,A6,Lm6;
        D*H = ((K*A)*C")*H & G*E = ((I*A)*C")*E & K*H - I*E = 0.F
        by A3,A5,A6,A13,Lm6,VECTSP_1:88;
      hence D*H-G*E = 0.F by Lm8;
      thus D*I-G*K = 0.F by A3,A5,A6,A13,Lm6;
    end;
   hence ex g,h,k,l st [g,h,k,l] = [p,q,r,s] & CB[g,h,k,l] by A6;
  end;
  hence thesis by Th23;
 end;

theorem
Th27: a,b '||' a,c implies b,a '||' b,c
 proof assume a,b '||' a,c;

  then consider e,f,g,h such that
  A1:  [e,f,g,h] = [a,b,a,c] and
  A2:  (e`1-f`1)*(g`2-h`2) - (g`1-h`1)*(e`2-f`2) = 0.F &
       (e`1-f`1)*(g`3-h`3) - (g`1-h`1)*(e`3-f`3) = 0.F &
       (e`2-f`2)*(g`3-h`3) - (g`2-h`2)*(e`3-f`3) = 0.F by Th23;
    e = a & f = b & g = a & h = c by A1,MCART_1:33;
  then [f,e,f,h] = [b,a,b,c] &
  (f`1-e`1)*(f`2-h`2) - (f`1-h`1)*(f`2-e`2) = 0.F &
  (f`1-e`1)*(f`3-h`3) - (f`1-h`1)*(f`3-e`3) = 0.F &
  (f`2-e`2)*(f`3-h`3) - (f`2-h`2)*(f`3-e`3) = 0.F by A2,Lm13;
  hence b,a '||' b,c by Th23;
 end;

theorem
Th28: ex d st a,b '||' c,d & a,c '||' b,d
 proof
     the carrier of MPS(F) = 3F(F) by Th21;
  then consider e,f,g such that A1: e = a & f = b & g = c;
  set h = g+f+-e;
  reconsider d = h as Element of MPS(F) by Th21;
  take d;
    g+f = [g`1+f`1,g`2+f`2,g`3+f`3] & -e = [-e`1,-e`2,-e`3] by Th3,Th7;
  then h = [g`1+f`1+-e`1,g`2+f`2+-e`2,g`3+f`3+-e`3] by Th4;
  then A2: h`1 = g`1+f`1+-e`1 & h`2 = g`2+f`2+-e`2 & h`3 = g`3+f`3+(-e`3)
    by MCART_1:47;
  then [e,f,g,h] = [a,b,c,d] &
  (e`1-f`1)*(g`2-h`2) - (g`1-h`1)*(e`2-f`2) = 0.F &
  (e`1-f`1)*(g`3-h`3) - (g`1-h`1)*(e`3-f`3) = 0.F &
  (e`2-f`2)*(g`3-h`3) - (g`2-h`2)*(e`3-f`3) = 0.F by A1,Lm15;
  hence a,b '||' c,d by Th23;
    [e,g,f,h] = [a,c,b,d] &
  (e`1-g`1)*(f`2-h`2) - (f`1-h`1)*(e`2-g`2) = 0.F &
  (e`1-g`1)*(f`3-h`3) - (f`1-h`1)*(e`3-g`3) = 0.F &
  (e`2-g`2)*(f`3-h`3) - (f`2-h`2)*(e`3-g`3) = 0.F by A1,A2,Lm15;
  hence thesis by Th23;
 end;

::
::                  3. DEFINITION OF PARALLELITY SPACE
::

definition let IT be non empty ParStr;
 attr IT is ParSp-like means
 :Def12: for a,b,c,d,p,q,r,s being Element of IT
          holds a,b '||' b,a & a,b '||' c,c & (a,b '||' p,q & a,b '||' r,s
          implies p,q '||' r,s or a=b) & (a,b '||' a,c implies b,a '||' b,c)
          & (ex x being Element of IT st
          a,b '||' c,x & a,c '||' b,x);
end;

definition
 cluster strict ParSp-like (non empty ParStr);
  existence
   proof consider F;
       for a,b,c,d,p,q,r,s being Element of MPS(F)
     holds a,b '||' b,a & a,b '||' c,c & (a,b '||' p,q & a,b '||' r,s
     implies p,q '||' r,s or a=b) & (a,b '||' a,c implies b,a '||' b,c)
     & (ex x being Element of MPS(F) st
     a,b '||' c,x & a,c '||' b,x) by Th24,Th25,Th26,Th27,Th28;
     then MPS(F) is ParSp-like by Def12;
    hence thesis;
   end;
end;

definition
 mode ParSp is ParSp-like (non empty ParStr);
end;

reserve PS for ParSp, a,b,c,d,p,q,r,s for Element of PS;

canceled 6;

theorem
Th35: a,b '||' a,b
proof b,a '||' b,b by Def12; hence a,b '||' a,b by Def12; end;

theorem
Th36: a,b '||' c,d implies c,d '||' a,b
proof assume A1: a,b '||' c,d;
  a,b '||' a,b by Th35; then a<>b implies c,d '||' a,b by A1,Def12;
hence thesis by Def12; end;

theorem
Th37: a,a '||' b,c
proof b,c '||' a,a by Def12; hence a,a '||' b,c by Th36; end;

theorem
Th38: a,b '||' c,d implies b,a '||' c,d
proof assume A1: a,b '||' c,d;
  a,b '||' b,a by Def12; then a<>b implies b,a '||' c,d by A1,Def12;
hence thesis by A1; end;

theorem
Th39: a,b '||' c,d implies a,b '||' d,c
proof assume a,b '||' c,d; then c,d '||' a,b by Th36; then d,c '||'
 a,b by Th38;
hence a,b '||' d,c by Th36; end;

theorem
Th40: a,b '||' c,d implies
      b,a '||' c,d & a,b '||' d,c & b,a '||' d,c & c,d '||' a,b &
      d,c '||' a,b & c,d '||' b,a & d,c '||' b,a
proof assume a,b '||' c,d; then c,d '||' a,b by Th36;
then A1: d,c '||' a,b by Th38; then A2: d,c '||' b,a by Th39; then c,d '||'
 b,a by Th38;
hence thesis by A1,A2,Th36,Th38; end;

theorem
Th41: a,b '||' a,c implies
       a,c '||' a,b & b,a '||' a,c & a,b '||' c,a & a,c '||' b,a & b,a '||'
 c,a &
       c,a '||' a,b & c,a '||' b,a & b,a '||' b,c & a,b '||' b,c & b,a '||'
 c,b &
       b,c '||' b,a & a,b '||' c,b & c,b '||' b,a & b,c '||' a,b & c,b '||'
 a,b &
       c,a '||' c,b & a,c '||' c,b & c,a '||' b,c & a,c '||' b,c & c,b '||'
 c,a &
       b,c '||' c,a & c,b '||' a,c & b,c '||' a,c
proof assume A1: a,b '||' a,c; then A2: b,a '||' b,c by Def12;
     a,c '||' a,b by A1,Th36; then c,a '||' c,b by Def12;
hence thesis by A1,A2,Th40;end;

theorem
  a=b or c = d or a=c & b=d or a=d & b=c implies a,b '||' c,d
  by Def12,Th35,Th37;

theorem
Th43: a<>b & p,q '||' a,b & a,b '||' r,s implies p,q '||' r,s
proof assume a<>b & p,q '||' a,b & a,b '||' r,s;
then a<>b & a,b '||' p,q & a,b '||' r,s by Th40; hence thesis by Def12; end;

theorem
  not a,b '||' a,c implies a<>b & b<>c & c <>a by Def12,Th35,Th37;

theorem
    not a,b '||' c,d implies a<>b & c <>d by Def12,Th37;

canceled;

theorem
Th47: not a,b '||' a,c implies
 not a,c '||' a,b & not b,a '||' a,c & not a,b '||' c,a & not a,c '||' b,a &
 not b,a '||' c,a & not c,a '||' a,b & not c,a '||' b,a & not b,a '||' b,c &
 not a,b '||' b,c & not b,a '||' c,b & not b,c '||' b,a & not b,a '||' c,b &
 not c,b '||' b,a & not b,c '||' a,b & not c,b '||' a,b & not c,a '||' c,b &
 not a,c '||' c,b & not c,a '||' b,c & not a,c '||' b,c & not c,b '||' c,a &
 not b,c '||' c,a & not c,b '||' a,c & not b,c '||' a,c
proof assume A1: not a,b '||' a,c; assume not thesis;
 then a,c '||' a,b or a,b '||' a,c or a,b '||' a,c or a,c '||' a,b or a,b '||'
 a,c or
 a,c '||' a,b or a,c '||' a,b or b,a '||' b,c or b,a '||' b,c or b,a '||'
 b,c or
 b,c '||' b,a or b,a '||' b,c or b,c '||' b,a or b,c '||' b,a or b,c '||'
 b,a or
 c,a '||' c,b or c,a '||' c,b or c,a '||' c,b or c,a '||' c,b or c,b '||'
 c,a or
 c,b '||' c,a or c,b '||' c,a or c,b '||' c,a by Th40;
 hence contradiction by A1,Th41; end;

theorem
Th48: not a,b '||' c,d & a,b '||' p,q & c,d '||' r,s & p<>q & r<>s
  implies not p,q '||' r,s
proof assume A1: not a,b '||' c,d & a,b '||' p,q & c,d '||' r,s & p<>q & r<>s;
assume p,q '||' r,s; then a,b '||' r,s by A1,Th43;
then r,s '||' a,b & r,s '||' c,d by A1,Th40;
hence contradiction by A1,Def12; end;

theorem
Th49: not a,b '||' a,c & a,b '||' p,q & a,c '||' p,r & b,c '||' q,r & p<>q
implies not p,q '||' p,r
proof assume A1: not a,b '||' a,c & a,b '||' p,q & a,c '||' p,r & b,c '||'
 q,r & p<>q;
  now assume p=r; then p,q '||' b,a & p,q '||' b,c by A1,Th40;
then b,a '||' b,c by A1,Def12; hence contradiction by A1,Th41; end;
hence thesis by A1,Th48; end;

theorem
Th50: not a,b '||' a,c & a,c '||' p,r & b,c '||' p,r implies p=r
proof assume not a,b '||' a,c & a,c '||' p,r & b,c '||' p,r; then not
a,c '||' b,c & p,r '||' a,c & p,r '||' b,c by Th40,Th47; hence
  thesis by Def12; end;

theorem
Th51: not p,q '||' p,r & p,r '||' p,s & q,r '||' q,s implies r=s
proof assume not p,q '||' p,r & p,r '||' p,s & q,r '||' q,s;
then not r,p '||' r,q & r,s '||' r,p & r,s '||' r,q by Th47;
hence thesis by Def12; end;

theorem
   not a,b '||' a,c & a,b '||' p,q & a,c '||' p,r & a,c '||' p,s &
b,c '||' q,r & b,c '||' q,s implies r=s
proof assume A1:  not a,b '||' a,c & a,b '||' p,q & a,c '||' p,r & a,c '||'
 p,s &
b,c '||' q,r & b,c '||' q,s;
then A2: p=q implies p=r & p=s by Th50;
  now assume p<>q; then not p,q '||' p,r & a<>c & b<>c by A1,Def12,Th35,Th49;
then not p,q '||' p,r & p,r '||' p,s & q,r '||' q,s by A1,Def12;
hence thesis by Th51; end;
hence thesis by A2; end;

theorem
Th53: a,b '||' a,c & a,b '||' a,d implies a,b '||' c,d
proof assume A1:  a,b '||' a,c & a,b '||' a,d;
  now assume a<>b & a<>c; then a<>c & a,c '||' a,d by A1,Def12;
then a<>c & a,c '||' c,d by Th41; hence thesis by A1,Th43; end;
hence thesis by A1,Th37; end;

theorem
  (for a,b holds a=b) implies for p,q,r,s holds p,q '||' r,s
proof assume A1: for a,b holds a=b; let p,q,r,s;
  r=s by A1; hence thesis by Def12; end;

theorem
  (ex a,b st a<>b & for c holds a,b '||' a,c) implies for p,q,r,s holds p,q
'||'
 r,s
proof assume A1: ex a,b st a<>b & for c holds a,b '||' a,c;
let p,q,r,s; consider a,b such that A2: a<>b & for c holds a,b '||' a,c
by A1; a,b '||' a,p & a,b '||' a,q & a,b '||' a,r & a,b '||' a,s by A2;
then a,b '||' p,q & a,b '||' r,s by Th53; hence thesis by A2,Def12; end;

theorem
  not a,b '||' a,c & p<>q implies not p,q '||' p,a or not p,q '||'
 p,b or not p,q '||' p,c
proof assume A1: not a,b '||' a,c & p<>q;
assume A2: not thesis; then A3: a<>p by A1,Def12;
  p,a '||' p,b & p,a '||' p,c by A1,A2,Def12; then a,p '||' a,b & a,p '||'
 a,c by Th41;
hence contradiction by A1,A3,Def12; end;

Back to top